Zhihui Fang on SFL-Informed Literacy Education. (4th May 2021) - Fang, Zhihui; Gao, Yanmei; Yin, Chengzhu; Li, Hanbing
Abstract : As appliable linguistics, systemic functional linguistics (SFL) has been widely applied in various areas of education – in studies of classroom discourse, in teacher training, curriculum development, etc. Zhihui Fang is a leading scholar who has applied systemic functional linguistics in the development of pedagogical models for secondary literacy education. In this interview, Yanmei Gao, Chengzhu Yin and Hanbing Li ask Zhihui Fang about the applicability of systemic functional linguistics in literacy education, especially in the United States. They also discuss the possible influence of the new developments of the Sydney School, such as genre relations, on content areas teaching practice.